Rekonstruksi Moderasi Beragama Terintegrasi Sains Pondok Pesantren Era Revolusi Industri 4.0 - Muhammad Ilham Syarif; Saputra Habci Amran; Safrizal Safrizal; Niki Dian Permana; R Hariyani Susanti (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This research was conducted because of an interesting case that occurred at the Tajung Limau Islamic boarding school. The unique case that occurs is the integration effort that occurs between religious values and the effort to instill moderation in religion to manifest an attitude of tolerance. The research method used is a qualitative method with a case study model. The CSE study method is a qualitative research method which is carried out because of an interesting case that occurred in the community. Data collection was carried out by means of observation and interviews. Data analysis was performed using the triangulation method. The research results obtained are that moderation in religion has been carried out since planning, implementing and evaluating learning. Planting the values of religious moderation at the Thawalib Islamic Boarding School Tanjung Limau, Pariangan District, is carried out by incorporating the values contained in the concept of moderation. So that the effort made is an effort to integrate science with religion. Integration in science learning is done by connecting verses of the Koran with science concepts such as Al-hujurat verse 13 about diversity.